Factors Influencing High Fly Density at Food Vendors - Tri Wahyuni Pratiwi; Dini Arista Putri; Inoy Trisnaini; Rafika Oktivaningrum; Imelda Gernauli Purba (Jurnal Ilmu Kesehatan Masyarakat, 2025)
Palembang, as a rapidly expanding culinary destination, faces increased vulnerability to food contamination, particularly in the Ampera Bridge culinary area where dense vendor activity, inadequate sanitation, and proximity to pollution sources create favorable conditions for vector proliferation. Flies function as mechanical vectors capable of transmitting pathogens to food, posing a substantial public health risk. This study aimed to analyze environmental factors associated with fly density among food vendors around the Ampera Bridge. An analytical observational study with a cross-sectional design was conducted in November 2024. Fly density was measured using the Ministry of Health’s fly grill method and categorized into low, medium, and high. Independent variables included food serving area condition, trash can condition, sink condition, location, fly prevention facilities, temperature, and humidity. A total of 103 vendors meeting the inclusion criteria were selected through purposive sampling. Univariat analysis showed that most vendors had poor serving areas, trash cans, and fly prevention facilities. Bivariate analysis indicated that only vendor location and preventive facilities were significantly associated with high fly density. Multivariate analysis further demonstrated that inadequate fly prevention facilities were the strongest predictor of high fly density, followed by vendor location. The study concludes that preventive facilities and vendor proximity to pollution sources are key determinants of fly density. Strengthening sanitation practices and improving environmental hygiene infrastructure are recommended to reduce fly density and mitigate foodborne disease risk.